What to teach about earth sciences in early childhood education?: A curriculum analysis - Irene Prieto Saiz; Beatriz García Fernández; José Reyes Ruiz-Gallardo (Journal of Technology and Science Education)
Scientific content is addressed in schools from the early stages of education. Among these, those related to Earth Sciences provide an understanding of the environment that makes them crucial for facing the new challenges that society confronts. The early childhood education stage is considered ideal for an initial approach to understanding our planet, thereby laying a foundation upon which to build future knowledge. The present study aims to analyse aspects related to Earth Sciences and their treatment in the current Spanish educational law for this stage. To achieve this, a content analysis methodology was employed to examine the law. The results conclude that various fundamental concepts could be introduced in the preschool classroom through Earth Sciences. However, in many instances, the wording of the law refers to science in a general sense, leaving it to the discretion of educators to decide whether to address them in early childhood education. In this context, teacher training is crucial to provide educators with the knowledge and skills necessary to address these concepts in this educational stage.